Removal of E. coli O157:H7 coliform bacteria from sewage wastewater using silver doped borate bioglass - Bassant I. Elsaba; Ashraf Elsayad; Yasser S. Rammah; Hosam Salaheldin (Scientific Reports)
Abstract The depletion of freshwater resources constitutes a significant global issue, prompting the consideration of treated sewage wastewater (SWW) reuse as a viable alternative water source within contemporary water management strategies. The current study represents an innovative silver borate-based bioglass (BG) system for the treatment of municipal SWW. The melting-quenching method was used to prepare silver doped BG samples with different Ag2O concentrations. BAg1, BAg2, BAg3, and BAg4 BG samples were obtained from (65-X) B2O3–20Na2O–10CaO–5P2O5–XAg2O (where X = 0, 1, 2, 3, and 4 mol%). A major fecal coliform bacterium, Escherichia coli O157:H7 (E. coli O157:H7), was used as an indication of SWW purification. BG samples were characterized using FTIR, XRD, SEM, EDX, and DLS, respectively. BAg1 BG sample showed the strongest antibacterial activity against E. coli O157:H7, with a 27.0 ± 1.0 mm inhibition zone and 95.31% growth inhibition. Compared to other BG samples, the inhibition zone diameter was marginally lower than the amoxicillin positive control (28.33 ± 0.1 mm). Additionally, all BG samples inhibit the coliform bacterial community approximately 100%., whereas the original BG sample (BAg0) did not inhibit coliform bacteria. All BG samples had minimum inhibition concentrations (MICs) of 5 mg/mL and minimum bactericidal concentrations (MBCs) of 50 mg/mL, respectively, compared to the untreated bacterial culture (− Ve control). SEM micrographs showed that BAg1 sample treated E. coli O157:H7 cells deteriorated more than BAg0. In conclusion, silver-doped BG is a cost-effective, eco-friendly, and highly recommended technology for SWW purification from fecal coliform bacteria and therefore, can be used for reclamation and other non-drinking water.